Discourses about Fake News, Conspiracies and Counterknowledge in Spain - Fernández-García, Belén (2022)
This research addresses the role of populist parties as disinformation agents. It specifically focuses on their use of Twitter to challenge the traditional authorities of knowledge and sources of information. The analysis relies on a content analysis of tweets to identify 1) the strategies employed to contest the “truth”; 2) the alternative sources of knowledge and information proposed; 3) the specific issues mentioned in those tweets and used to substantiate such strategies. Our findings confirm the relevance of these discourses and strategies in the populist parties’ tweets and particularly in the radical right.